Practices of the Semester System in Higher Education: Insights from the University of Nepal - Khatri, Ramesh (KMC Journal, 2026)
The semester system is an innovative approach to education that differs from the annual system. It emphasizes continuous student assessment, a flexible and market-driven curriculum, and learner-centered teaching methods. This study examines the implementation of a semester system at Valley University (pseudonym), Nepal. A mixed-methods approach was employed to gather quantitative data from 43 faculty members via a Google form, with seven faculty members chosen for in-depth interviews across five graduate schools at VU. The findings show that while faculty members view the semester system as a modern and innovative approach to higher education, its complete success is challenged by insufficient infrastructure, inconsistent academic calendars, irregular student attendance, inadequate teaching and learning resources, poor time management, an under-resourced library, and limited professional development opportunities for teachers. Faculty members discussed the need for curriculum revision and redesign to meet market-driven demands, effective administrative management, and the proper integration of technology in teaching and research. The study concludes that policy formulation, including the effective implementation of the semester system, teacher capacity building through professional development, and infrastructure investments, is necessary for the semester system to achieve its goals. The study’s findings can improve existing practices and facilitate knowledge sharing among key university stakeholders.